2018
DOI: 10.3389/fgene.2018.00497
|View full text |Cite
|
Sign up to set email alerts
|

SNPs Associated With Testosterone Levels Influence Human Facial Morphology

Abstract: Many factors influence human facial morphology, including genetics, age, nutrition, biomechanical forces, and endocrine factors. Moreover, facial features clearly differ between males and females, and these differences are driven primarily by the influence of sex hormones during growth and development. Specific genetic variants are known to influence circulating sex hormone levels in humans, which we hypothesize, in turn, affect facial features. In this study, we investigated the effects of testosterone-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 54 publications
0
32
0
7
Order By: Relevance
“…Notably, however, a small number of studies have found that facial masculinity correlates with another proxy of circulating testosterone – physical strength among both men [40, 41] and women [35, 42]. It is highly likely that all the above-described associations relate to genetic differences in testosterone production as genetic variants that are associated to higher testosterone levels in the body are also associated with facial masculinity [43].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, however, a small number of studies have found that facial masculinity correlates with another proxy of circulating testosterone – physical strength among both men [40, 41] and women [35, 42]. It is highly likely that all the above-described associations relate to genetic differences in testosterone production as genetic variants that are associated to higher testosterone levels in the body are also associated with facial masculinity [43].…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone has been suggested as the primary mediator of the fWHR and aggression relationship [7,16,22]; however, several study results did not support this suggestion [4,22]. In a recent genetics study, three SNPs associated with the testosterone levels in the body were reported to have an apparent effect on mandible shape and fWHR [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many craniofacial properties show dimorphism between sexes; for instance, males are known for the broader zygomatic region, supraorbital ridge, and prominent mandibula, while females have longer and narrower faces, rounder and broader foreheads, and thicker lips compared to males [24,30]. In addition to the age, nutrition, biomechanical forces, the endocrine factors, especially pubertal sex hormones, have been established as the primary influencers of masculinization and feminization of craniofacial features [30]. The influence of pubertal testosterone was shown on facial width/lower facial height and cheekbone prominence decrease, and lower face height/full face height increase [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although functional magnetic resonance imaging (fMRI) analysis refutes claims of the former's moderation effect on emotion-processing functions in males (Ma et al, 2017), the latter has been shown to inhibit affective empathy (Crespi, 2016;Nitschke & Bartz, 2020) and cognitive appraisal processing (Carré et al, 2015;Herbert, 2018) in both males and females by modulating information flows between the amygdala and forebrain structures such as the vmPFC (Chen et al, 2016). Additionally, genetics research demonstrates a significant mediation effect of testosterone on sexually-dimorphic arrangements of various craniofacial structures (Roosenboom et al, 2018), including fWHR (Weinberg et al, 2015). Ergo, it is not without precedent to suggest that increased levels of testosterone may account for the higher externally-attributed ratings of masculinity and malevolent aggression in high-psychopathy facial composites (e.g., Lyons et al, 2015;cf.…”
Section: The Case For Successful Psychopathymentioning
confidence: 99%